The learner’s brain cannot be fooled – a vicious circle of didactic assumptions - Bielecki, Robert (Annales Universitatis Paedagogicae Cracoviensis. Studia ad Didacticam Scientiarum Socialium Pertinentia, 2022)
The article presents chosen areas of didactics, pointing at the inadequacy of a part of teaching proposed at schools to students’ natural abilities resulting from the mechanisms of the working brain. It also shows its selected mechanisms in the perspective of their practical influence on the learning process. Contemporary didactics requires active transposition of the knowledge of the working brain to its ground in order to understand the mind better. It is essential for the teacher to be updated on the understanding of the informative functions of the brain such as gaining, collecting, processing and generating knowledge. The teacher, understanding the learning brain mechanisms, will be able to construct the teaching process in a more conscious way.